SMCHD1 mutation spectrum for facioscapulohumeral muscular dystrophy type 2 (FSHD2) and Bosma arhinia microphthalmia syndrome (BAMS) reveals disease-specific localisation of variants in the ATPase domain. Issue 10 (26th June 2019) - Lemmers, Richard J L F; van der Stoep, Nienke; Vliet, Patrick J van der; Moore, Steven A; San Leon Granado, David; Johnson, Katherine; Topf, Ana; Straub, Volker; Evangelista, Teresinha; Mozaffar, Tahseen; Kimonis, Virginia; Shaw, Natalie D; et al.
Abstract : Background: Variants in the Structural Maintenance of Chromosomes flexible Hinge Domain-containing protein 1 ( SMCHD1 ) can cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) and the unrelated Bosma arhinia microphthalmia syndrome (BAMS). In FSHD2, pathogenic variants are found anywhere in SMCHD1 while in BAMS, pathogenic variants are restricted to the extended ATPase domain. Irrespective of the phenotypic outcome, both FSHD2-associated and BAMS-associated SMCHD1 variants result in quantifiable local DNA hypomethylation. We compared FSHD2, BAMS and non-pathogenic SMCHD1 variants to derive genotype–phenotype relationships. Methods: Examination of SMCHD1 variants and methylation of the SMCHD1-sensitive FSHD locus DUX4 in 187 FSHD2 families, 41 patients with BAMS and in control individuals. Analysis of variants in a three-dimensional model of the ATPase domain of SMCHD1. Results: DUX4 methylation analysis is essential to establish pathogenicity of SMCHD1 variants. Although the FSHD2 mutation spectrum includes all types of variants covering the entire SMCHD1 locus, missense variants are significantly enriched in the extended ATPase domain. Identification of recurrent variants suggests disease-specific residues for FSHD2 and in BAMS, consistent with a largely disease-specific localisation of variants in SMCHD1. Conclusions: The localisation of missense variants within the ATPase domain of SMCHD1 may contribute to the differences in phenotypic outcome.